(untitled) (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Carcinoma (Ca) of the gallbladder is a rare disease. But its prognosis is poor. Early diagnosis of Ca gallbladder, though important, is rarely achieved due to lack of symptoms and physical signs. However, it is frequently associated with gallstone diseases. It is, therefore, of utmost importance to do a routine histopathological examination of all gallbladder specimens after cholecystectomy is done for gallstone diseases. The present study was undertaken to find the prevalence of Ca gallbladder in gallstone diseases. Methods: This descriptive study was conducted in the Department of Surgery, BSMMU Hospital, and in the Public Medical College Hospitals of Dhaka over a period of eight months from July 2011 to February 2012. A total of 1012specimens of gallbladder were taken from the patients who underwent either laparoscopic or open cholecystectomy for gallstone diseases in the above-mentioned hospitals during the study period. Following the operation, the resected specimens or the biopsies taken from the gallbladder were collected in 10% formaldehyde solution and were sent to the Histopathology Departments of the respective hospitals, for confirmation of diagnoses as well as for histological grading and typing. Result: Of the 1012 cases of operated gallbladder for cholelithiasis, 28(2.7%) cases were histopathologically diagnosed as having Ca gallbladder. The age incidence of Ca gallbladder varied from 43 – 71 years. The highest incidence was observed in the 6th decade (53.6%) followed by the 5th decade of life (28.5%). Out of 28 cases of Ca gallbladder, 15(53.6%) exhibited increased wall thickness. All 28 cases were adenocarcinoma; of them, 25(89.3%) were poorly differentiated and 3(10.7%) were well-differentiated carcinoma. Non-squamous cell carcinoma or other variants were found. The majority (82.1%) of the cases was of infiltrative scirrhous (a hard slow-growing malignant tumor having a preponderance of fibrous tissue) type and the rest (17.9%) fungating type. Staging of the disease stratified 4(14.3%) cases as Stage-IV, 3(10.7%) cases as Stage-Ill, 8(28.6%) cases as Stage-II, and 13(46.4%) cases of Stage-I. Conclusion: The study concluded that the prevalence of malignancy in gallstone disease is rare. The incidence is highest in the 6th decade of life and females are more often affected than males. As older people with gallstone diseases are at increased risk of having gallbladder malignancy, it is imperative that older patients with gallstone diseases should be routinely examined for evidence of carcinoma. Ibrahim Card Med J 2022; 12 (2): 59-63